2020
DOI: 10.1002/dc.24609
|View full text |Cite
|
Sign up to set email alerts
|

How useful are cervical Pap smears in detecting endometrial carcinomas? A tertiary cancer center experience

Abstract: Objective To determine the role of routine cervical Pap smears in detecting endometrial carcinomas. Method A retrospective study was carried out from the histopathology archives for cases diagnosed as endometrial carcinomas with Pap smears within 6 months before histological diagnosis. The demographic details, reports of Pap smears and other tumor parameters on histopathology were noted. Results We identified 380 of 482 cases of endometrial carcinoma with a documented Pap smear within 6 months before histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In our study, a total of 12.1% cytological abnormalities were found in 423 patients, 18% of whom were non-endometrioid type tumors, and a borderline significance was found between cervical stromal involvement and smear abnormality. Mehta et al [12] found preoperative abnormal cytology in 49% of 380 patients. Gu M et al [13] evaluated 76 patients in their study, while abnormal Pap smear was associated with FIGO stage, they found no association with age, MI, and LVSI.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, a total of 12.1% cytological abnormalities were found in 423 patients, 18% of whom were non-endometrioid type tumors, and a borderline significance was found between cervical stromal involvement and smear abnormality. Mehta et al [12] found preoperative abnormal cytology in 49% of 380 patients. Gu M et al [13] evaluated 76 patients in their study, while abnormal Pap smear was associated with FIGO stage, they found no association with age, MI, and LVSI.…”
Section: Discussionmentioning
confidence: 98%
“…The sensitivity of liquid-based cytology (LBC) in detecting endometrial carcinoma ranges from 31.9% to 89.6%. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…Yet only 5% to 10% of patients with this common alarming symptom have an underlying malignancy 9 . Another small subset of asymptomatic endometrial cancer patients is detected via a Pap smear obtained during cytology‐based cervical cancer screening or other indications 10‐12 . As cervical cancer screening programs have shifted from cytology to primary testing for human papillomavirus (HPV) in many countries today, the detection of asymptomatic endometrial cancers via Pap testing is declining 13 …”
Section: Introductionmentioning
confidence: 99%
“…9 Another small subset of asymptomatic endometrial cancer patients is detected via a Pap smear obtained during cytology-based cervical cancer screening or other indications. [10][11][12] As cervical cancer screening programs have shifted from cytology to primary testing for human papillomavirus (HPV) in many countries today, the detection of asymptomatic endometrial cancers via Pap testing is declining. 13 Besides the detection of endometrial cancer in Pap smears, recent cytology research demonstrates that endometrial cancer cells are detectable in vaginal samples 14 and urine 15 by shedding through the cervix into the vaginal debris.…”
Section: Introductionmentioning
confidence: 99%